A Survey on Present Mobile Ad-Hoc Networks (MANET) Security: Securing Mobile Ad-Hoc Networks: Routing, Data Security, and Intrusion Detection (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The wireless mobile nodes are capable to build spontaneously temporary wireless network in absence of infrastructure like AP, Router etc. and they act as a wireless router. Due to this, wireless mobile nodes are capable for forwarding messages to other nodes. MANET (Mobile Adhoc Network) is a one of the wireless network and forms a temporary connection across the mobile nodes without central infrastructure to exchange the information. Due to the characteristics of MANET, it is vulnerable to active and passive attacks from internal and external attacker. This will lead to various security challenges. There is a requirement to secure the MANET from threats and vulnerability. Many security mechanisms are established to secure and protect the MANET. This article is intended to provide contemporary MANET security with perspective of routing protocol security and data security with key management, and monitoring the MANET during routing andor data transmission using IDS (Intrusion Detection System). This article presents the various attacks face by MANET and its security goals. The article explored various security solutions for routing protocols, data security using cryptography as a first line of defence, key management for securing communication. It also explored various IDS schemes as a second line of defence in MANET.